Attitude Does Not Moderate Influence Perceived Ease of Use, Perceived Usefulness, and Perceived Risk on The Adoption of Fintech Technology - Uke Prajogo; Vera Wanda Nena Feronika (Universitas Merdeka Malang, 2026)
This study aims to determine the effect of Perceived Ease of Use, Perceived Usefulness, and Perceived Risk on the adoption of fintech technology with attitude as a moderating variable. The type of research used is explanatory research. The sample in this study were 91 respondents, students of STIE Malangkucecwara who have businesses. The research sample is a saturated sample. The research instrument used a questionnaire and observation. The analysis used Partial Least Squares Structural Equation Modeling (PLS-SEM), where X1 refers to the variable Perceived Ease of Use, X2 to the variable Perceived Usefulness, X3 to the variable Perceived Risk, Z to the variable Attitude and Y to the variable Adoption of fintech technology. Based on the results of the study, it was concluded that Perceived Ease of Use, Perceived Usefulness, and Perceived Risk were proven to have a positive and significant effect on the adoption of Byond by BSI fintech technology. Attitude was not proven to moderate the influence of Perceived Ease of Use, Perceived Usefulness, and Perceived Risk on the adoption of Byond by BSI fintech technology.